2015
DOI: 10.1080/15427951.2014.925524
|View full text |Cite
|
Sign up to set email alerts
|

Long Paths in Random Apollonian Networks

Abstract: We consider the length L(n) of the longest path in a randomly generated Apollonian Network (ApN) A n . We show that with high probability L(n) ≤ ne − log c n for any constant c < 2/3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…After t steps, we obtain a random triangulated plane graph with t + 3 vertices, which is called a random Apollonian network. We prove that there exists a fixed δ < 1, such that eventually every path in this graph has length less than t δ , which verifies a conjecture of Cooper and Frieze (2015). …”
supporting
confidence: 51%
See 1 more Smart Citation
“…After t steps, we obtain a random triangulated plane graph with t + 3 vertices, which is called a random Apollonian network. We prove that there exists a fixed δ < 1, such that eventually every path in this graph has length less than t δ , which verifies a conjecture of Cooper and Frieze (2015). …”
supporting
confidence: 51%
“…Frieze and Tsourakakis [7] conjectured that there exists a fixed δ > 0 such that P(δt ≤ L t < t) → 1. Ebrahimzadeh et al [6] refuted this conjecture and showed that there exists a fixed δ > 0 such that P(L t < t/(log t) δ ) → 1. Cooper and Frieze [3] improved this result by showing that, for every constant c < 2 3 , we have P(L t ≤ t exp(− log c t)) → 1, and conjectured that there exists a fixed δ < 1 such that P(L t ≤ t δ ) → 1. The second main result of this paper is the following, which in particular confirms this conjecture.…”
Section: Theorem 1 There Exists a Fixed δ < 1 Such That S T < T δ Evmentioning
confidence: 99%
“…Some aspects of Apollonian networks have been investigated in [4]- [6] and [9]. We were inspired by these very recent works to investigate additional properties.…”
Section: Scope and Resultsmentioning
confidence: 99%
“…We also numerically study the Wiener index, and conjecture that its limiting distribution is not normal based on simulation results. The diameter of HDRANs is retrieved from [14].…”
Section: Discussionmentioning
confidence: 99%
“…The study of RAN first appeared in [55], where the power-law and the clustering coefficient were investigated. From then on, many more properties of RANs were uncovered by applied mathematicians and probablists: The degree distribution was characterized by [24]; the diameter was calculated by [21,24]; the length of the longest path in RANs was determined by [12,14,21]. All these resources, however, only focused on planar RANs, the evolution of which is based on continuing triangulation.…”
Section: Introductionmentioning
confidence: 99%